Molecular Mechanisms by Which S100A4 Regulates the Migration and Invasion of PGCCs With Their Daughter Cells in Human Colorectal Cancer - Fei, Fei; Liu, Kai; Li, Chunyuan; Du, Jiaxing; Wei, Zhen; Li, Bo; Li, Yuwei; Zhang, Yi; Zhang, Shiwu (Frontiers in Oncology, 2020)
Recently, an increasing number of evidences have shown that polyploid giant cancer cells (PGCCs) could generate daughter cells with a strong migration and invasion ability, which have been implicated in cancer recurrence and metastasis. However, the underlying molecular mechanisms remain largely unclear. In vitro and in vivo experiments combined with 222 cases of human colorectal cancer (CRC) samples were used to identify the molecular mechanisms of S100A4-related proteins regulating the invasion and metastasis of PGCCs with their daughter cells. PGCCs with their daughter cells had high migration, invasion, and proliferation abilities compared to control cells; these were significantly inhibited after S100A4 knockdown. The high expression of cathepsin B, cyclin B1, TRIM21 and Annexin A2 were significantly downregulated after S100A4 knockdown, while the overexpression of S100A4, cathepsin B, cyclin B1 and S100A10 were significantly downregulated after TRIM21 knockdown in PGCCs with their daughter cells. The tumorigenesis and metastasis ability of PGCCs with their daughter cells was significantly stronger than that of the untreated control cells in vivo, which was significantly decreased after S100A4 knockdown. Moreover, the expression of S100A4-related proteins was positively correlated with the malignancy degree of human CRC, and maintained a high level in lymph node metastasis. S100A4 and TRIM21 may regulate each other to affect the expression and subcellular localization of cyclin B1 involved in the formation of PGCCs with their daughter cells, which participates in regulating the structure and function of Annexin A2/S100A10 complex, affecting downstream cathepsin B, resulting in the invasion and metastasis of PGCCs with their daughter cells. Besides, 14-3-3 ζ/δ and Ezrin may be involved in the motility and invasion of PGCCs with their daughter cells via cytoskeletal constructions with S100A4.